Peran Ekstrakurikuler Berbasis Keagamaan Islam terhadap Pengembangan Sikap Kepedulian Sosial Siswa - Kusuma, Afri; Sumirah, Sumirah; Sukarno, Sukarno (Al-Miskawaih: Journal of Science Education, 2024)
Abstract This research aims to reveal the role of Islamic religious-based extracurricular activities in developing students' social awareness attitudes at the Madrasah Tsanawiyah Laboratory in Jambi City. This research uses a qualitative approach with data collection carried out using data analysis techniques including data reduction, data presentation, and researcher participation. Triangulation techniques using various sources, theories and methods and diligent observation. Researcher information is the school principal, teachers in the field of religious activities and students. The results of this research are that the implementation of religious activities at the Madrasah Tsanawiyah Laboratory has been running quite well, but improvements still need to be made so that all the expected goals can be achieved optimally. This can be seen from the results of observations, interviews, and documents that researchers obtained in the field. So this research can help teachers or educators not to underestimate the obligatory worship and sunnah of students, especially to make themselves good role models for students. Penelitian ini bertujuan untuk mengungkapkan Peran Ekstrakurikuler Berbasis Keagamaan Islam Terhadap Pengembangan Sikap Kepedulian Sosial  Siswa Di Madrasah Tsanawiyah Laboratarium Kota Jambi. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data dilakukan dengan teknik analisis data meliputi reduksi data, penyajian data, keikutsertaan peneliti. Teknik triangulasi dengan menggunakan berbagai sumber, teori dan metode dan ketekunan pengamatan. Informasi peneliti yaitu Kepala sekolah, Guru bidang kegiatan Keagamaan dan siswa. Hasil dari penelitian ini adalah pelaksanaan kegiatan keagamaan di Madrasah Tsanawiyah Laboratarium sudah berjalan dengan cukup baik, namun tetap perlu adanya peningkatan agar semua tujuan yang di harapkan dapat tercapai secara optimal. hal tersebut dapat dilihat dari hasil observasi, wawancara, serta dokumen yang peneliti dapatkan di lapangan. Sehingga dengan adanya penelitian ini dapat membantu guru atau pendidik untuk tidak menyepelekan ibadah wajib maupun sunahpada siswa khususnya menjadikan diri sebagai suri tauladan yang baik bagi peserta didik.